SENGKETA TANAH SETRA DAN PENYELESAIANNYA (STUDI KASUS SENGKETA BANJAR ADAT AMBENGAN DENGAN BANJAR ADAT SEMANA UBUD KABUPATEN GIANYAR) - Sri Haryanti Dewi Witari, I Gusti Ayu; Wirta Griadhi, I Ketut; Oka Parwata, A. A. Gde (Kertha Desa, 2013)
Dispute of grave land (setra) was occurred at customary village of Ambengan with customary village of Semana on 31 May 2007, its began from cutting of three coconut tree and one blalu tree at setra area by the member of customary village of Semana but didn’t got permit from the member of the customary village Ambengan, the incident more and more develop until happened physical contact and each others claim about ownership of the grave land. The incidence arise a question what was its background and what factors that influence the dispute of grave land? and how is its solution and its implementation?.The method have been used is emperical juridic with case, fact, and history approach to know the existing problem. Its solution was by conduct mediation by the government of Gianyar regency by issued a affirmation letter until signed an harmony by both parties.
Keywords: Dispute, Land, Setra, Customary